The metaverse and Islamic financial contracts: the case of Ijarah - Adam Sa'ad, Auwal; Rehan, Raja; Usman, Abubakar Abubakar; Salaudeen, Adnan Opeyemi (Taylor & Francis, 2023)
The metaverse is a virtual world that exists alongside the actual world. While the actual world refers to the real, physical world, the metaverse is a digital world that is accessed through technology. Evidently, several international brands have integrated their businesses with the virtual metaverse providing business opportunities. However, there are currently several gaps in the sector of Shariah finance that need to be addressed in order to take full advantage of the potential of the metaverse. For instance, rare studies enlighten the concept of Ijarah, a substitute for conventional leasing in the metaverse virtual world. Undoubtedly, the metaverse has the potential to revolutionize the Shariah finance industry by providing new opportunities for financial inclusion and innovation. Therefore, for the readiness of Islamic finance institutions, this study is an attempt to explore the possibility of executing Shariah principles that could be utilized in the metaverse. More specifically, this study is an endeavor to explore and discuss how Shariah-based leasing i.e., Ijarah integrates with the recent metaverse technologies. Additionally, this study also discusses the metaverse evolution and its integration into international business brands, the metaverse virtual assets ownership, the metaverse virtual leasing, non-fungible tokens (NFTs), and virtual real estate in the metaverse. Indeed, this study is a novel addition to the Shariah finance literature, which helps policymakers to generate new strategies that guide the execution of Ijarah contracts in the virtual universe of the metaverse.